The effectiveness of network performance in marketing homestay from the operators' point of view / Rafidah Abas - Abas, Rafidah (2012)
Homestay is a program where tourists stay with the host family to experience the distinct and unique lifestyle of the hosts directly and indirectly. This community based rural tourism product is aimed at supporting rural economic development. However, the success of the program is in doubt owing to poor professional marketing. Networking with the tourist organizations in marketing homestays raises the issue of the effectiveness of the network performance. As such, this research aimed to (i) identify the effectiveness of network performance in marketing homestays from the perspective of the operators, (ii) identifying the relationship between network performance and network performance effectiveness and (iii) to evaluate the differences between demographic profiles and the perception of network performance effectiveness. Employing the quantitative method, 208 samples were randomly selected from seven homestays in Selangor and Negeri Sembilan which have been operating for at least three years and consistently receive visitors throughout the year. Both parametric and non-parametric statistics were employed to compare and complement the results in exploring the relationship among the variables as well as the differences among groups. Findings revealed that respondents agreed that all the four variables under the performance dimension were important in contributing to network effectiveness. There is a weak, positive relationship between network performance and network performance effectiveness. Network performance was found effective in marketing homestays. Findings also indicated that gender is not significant in explaining the perceptions of homestay operators towards the effectiveness of network performance. Operators around the age of 32-58 years perceived that network performance is effective as opposed to the other three groups. Length of involvement however was insignificant to explain the differences in effectiveness. Understanding how the networks work provides direction to the actors to stay and act accordingly and learn how to sustain the relationship and determinants are essential for the networks to survive. Factors such as demographic, spatial or geographical location, as well the critical success factors themselves could play a major role in determining the success or failure of any performance as perceived by the operators. The inputs rendered are valuable for the tourist organizations in developing, marketing and managing the program effectively and efficiently.